(untitled) (International Journal of Environmental Sciences, 2025)
Low tension distribution systems, integral components of the electrical power grid, face persistent challenges, including overloading, technical losses, and delayed fault detection. Traditional passive networks struggle to meet the demands of modern energy consumption, compounded by the rise of distributed generation. Additionally, the prevalence of energy theft further undermines the efficiency and reliability of these systems. This paper addresses these challenges through the development of a cost-effective real-time monitoring system. By strategically placing sensor nodes within the distribution network, we aim to collect precise data on three-phase voltages, currents, and neutral currents. The incorporation of GPS transceivers ensures accurate location data and time synchronization. Utilizing LoRa technology for data transmission, our solution seamlessly integrates with existing infrastructure, providing real-time monitoring and control capabilities. This transformation is crucial for addressing grid challenges such as delayed fault de- tection and restoration. Furthermore, this work incorporates advanced metering ICs to enhance event detection, tackling the pervasive problem of energy theft. The proposed system offers a comprehensive solution by actively managing the distribution network, optimizing efficiency, and safeguarding against challenges unique to low tension distribution grids. Its cost-effective design allows for easy installation onto existing infrastructure, minimizing financial implications for utilities.